Conformations of ribonucleoside uridine in the low temperature Ar matrices - Ivanov, A.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The conformational equilibrium of the ribonucleoside uridine molecules in the low temperature Ar matrices was investigated by the FTIR matrix isolation spectroscopy and quantum-chemical calculations at the DFT and MP2 levels of theory. It was established that conformers with the carbonyl group C2O which takes part in the intramolecular hydrogen bonds dominate in the low temperature matrices. Populations of syn- and anti- conformers with intramolecular hydrogen bonds O5’H–O2 and O2’–O2, respectively, are equal practically. Unlike 2’-deoxyuridine, the syn-conformers of Ur with C3’-endo structure of the ribose ring (South) have been found in Ar matrices. At the same time the conformations of C2’-endo (North) ribose ring prevail both in anti- and syn-conformers.